A Note on the Hierarchical Model and Power Prior Distribution in Bayesian Quantile Regression - دخيل, طاهر ريسان (Journal of Economics and Administrative Sciences, 2014)
In this paper, we investigate the connection between the hierarchical models and the power prior distribution in quantile regression (QReg). Under specific quantile, we develop an expression for the power parameter ( ) to calibrate the power prior distribution for quantile regression to a corresponding hierarchical model. In addition, we estimate the relation between the  and the quantile level via hierarchical model. Our proposed methodology is illustrated with real data example.